Foregrounding Equity in Teacher Education: Toward a Model of Social Justice Pedagogical and Content Knowledge. (November 2017) - Dyches, Jeanne; Boyd, Ashley
Since its inception 30 years ago, Shulman's Pedagogical Content Knowledge (PCK) has fundamentally altered the landscape of teacher preparation. Despite its prominence in the field, the paradigm fails to delineate a space for the role of social justice in classroom practices and teacher preparation. Accordingly, we complicate the relationship between PCK and equitable teaching practices by forwarding Social Justice Pedagogical and Content Knowledge (SJPACK), a theoretical model segmented into three knowledge domains: Social Justice Knowledge, Social Justice Pedagogical Knowledge, and Social Justice Content Knowledge. Because all instructional maneuvers are politically charged and therefore never neutral, SJPACK advances Social Justice Knowledge as the foundational knowledge domain that permeates and shapes all PCK practices. Consequently, the framework posits that PCK can never be siloed from Social Justice Knowledge. Implications for SJPACK-oriented teacher preparation are discussed.